Desenvolvimento de um sistema para estimação de proficiência nas competências do curso de bacharelado em ciência da computação: uma aplicação da teoria da resposta ao item em turmas que usam sistemas gamificados - MONTEIRO, Rodrigo Henrique Barbosa (2019)
The Thirty Industrial Revolution brought the digital natives into the classroom, and this event intensified research and innovation efforts in teaching and assessment methodologies. In this context, gamification attracts by targeting a growing market. However, some empirical studies of its current state of art indicate that gamification brings benefits only in the short term, without causing significant changes in its continuous use. Therefore, the present work had as objective to analyze what the Classical Theory of Tests and the Item Response Theory can bring to the proposition of a competence learning measurement system in disciplines of the course of Bachelor in Computer Science that adopt gamification in the evaluation process, in order to contribute to the generation of psychometric data in a configurable experimentation environment: the software. In order to do so, an exploratory bibliographical research was carried out to define the concepts involved, as well as to find gamified educational systems that could have the same objective of this work. Of the twenty systems found, only three scored and stored the data that abstracted the learning, but without the indications of the approach of the Item Response Theory. Because of that, it was concluded that it was necessary to develop a system capable of estimating learning from this theory; which, in the future, integrating other gamified systems and storing the obtained data, will help fill the lack of empirical data in the area, in the medium and long term.